Temas ambientais como temas geradores: contribuições para uma metodologia educativa ambiental crítica, transformadora e emancipatória - Tozoni-reis, Marília Freitas De Campos [UNESP] (Setor de Educação da Universidade Federal do Paraná, 2006)
The emancipating and critical environmental education demands that knowledge must be adequate, build up in a dynamic, collective, cooperating, continuous, interdisciplinary, democratic and participating way directed to the construction of self-maintaining societies. This paper deals with environmental issues as generating issues for an environmental education inspired in Paulo Freire's pedagogy. According to him to educate is to know the reality in its experienced situations, as an ongoing critical process of closeness to the reality itself: to understand, to ponder, to criticize and to act are the intended pedagogical attitudes. The generating issues are strategic methods of a process of awareness about an oppressive reality in unequal societies. Such issues are the starting point to the process of building up a discovery. The generating issues spring out of the popular knowledge, taken from the daily life of the educating ones in order to replace the traditional contents. The political aspect of Paulo Freire's pedagogy are to be seen in the generating issues insofar as these ones contemplate the social and political contents that are meaningful to the life of the educating people. In this way all the educating proposals should take into consideration the local environmental issues as generating issues to the desired consciousness. Finally, it is important to say that the educating people should take part in defining and determining the issues that represent their interests as the content for an environmental and social action.

A educação ambiental crítica e emancipatória exige que os conhecimentos sejam apropriados, construídos, de forma dinâmica, coletiva, cooperativa, contínua, interdisciplinar, democrática e participativa, voltados para a construção de sociedades sustentáveis. Este artigo trata dos temas ambientais como temas geradores para a educação ambiental, inspirados na pedagogia Paulo Freire, para quem educar é um ato de conhecimento da realidade concreta, das situações vividas, um processo de aproximação crítica da própria realidade: compreender, refletir, criticar e agir são as ações pedagógicas pretendidas. Os temas geradores são, portanto, estratégias metodológicas de um processo de conscientização da realidade opressora vivida nas sociedades desiguais; são o ponto de partida para o processo de construção da descoberta, e, por emergir do saber popular, os temas geradores são extraídos da prática de vida dos educandos, substituindo os conteúdos tradicionais e buscados através da pesquisa do universo dos educandos. O caráter político da pedagogia freireana faz-se presente, de forma radical, nos temas geradores, isto é, temas geradores só são geradores de ação-reflexão-ação se forem carregados de conteúdos sociais e políticos com significado concreto para a vida dos educandos. Assim, as propostas educativas ambientais conscientizadoras podem tomar os temas ambientais locais como temas geradores desta ação conscientizadora, desde que estes temas contenham conteúdos socioambientais significativos para os educandos e sejam definidos coletiva e participativamente.
Environmental issues as generating issues: contributions to a critical, transforming and emancipating environmental educating methodology
Keywords: environmental issues; generating issues; environmental education methodology; awareness; temas ambientais; temas geradores; metodologia da educação ambiental; conscientização